Exploring the regional layout characteristics of ancient Chinese postal system in coastal areas based on AHP-CRITIC evaluation approach - Bei Wu; Lifeng Tan; Chang Cui (PLoS ONE, 2025)
In ancient China, as the only transmission network, the postal system enabled long-distance delivery of information and supplies, providing information support for the development of ancient society. Delivery efficiency determined whether information and supplies could arrive at the fastest speed, reflected the level of regional transmission capacity, and served as an effective indicator for understanding the underlying logic of the postal system’s regional layout. In this study, the concept of accessibility was introduced into the regional layout analysis of the postal system, and a hierarchical evaluation model was constructed based on the AHP-CRITIC (Analytic Hierarchy Process – Criteria Importance Though Intercriteria Correlation) composite weighting method. Then, the accessibility of the postal system in three typical areas of coastal defense front-line, transportation hub, and administrative center was qualitatively and quantitatively analyzed, and the differential characteristics of their accessibility and regional layout were summarized, so as to explore the layout logic of the postal system during the Ming Dynasty.